Care/Giving - Carpenter Estrada, Tara (Journal of the Motherhood Initiative for Research and Community Involvement, 2020)
Opening the creaky door to my room with a laundry basket balanced on one hip, I walked into the room and plopped the basket down on the bed. Startled by the noises, my infant daughter woke and started crying. I had forgotten that she was there. Lost in my own thoughts, I had momentarily wandered from my constant stream of thoughts about her. Has she eaten recently? When was her last diaper change? Is she happy? Becoming upset? In need of a nap? Children make themselves hard to forget—they have endless needs. Like a baton in a relay, someone must always take the responsibility for care. “Take a baby, leave a baby?” my husband jokingly asks as he hands her to me so he can Zoom into a meeting. Yes, I’ll take her. And I’ll leave her when it’s my turn to work again. Especially in this time of quarantine when we’re both working from home and childcare isn’t an option, we care for one another by trading off Baby. These images depict mundane everyday moments of caregiving. Using personal family photos as a starting point, I create line drawings with an image transfer process. The drawings are then painted in watercolor. Much like the way memories become muddled over time, the process used imperfectly replicates the images and introduces visual noise.